Answer:
![\boxed{\sf \ \ x = 9, \ y = -5, \ z = 5 \ \ }](https://img.qammunity.org/2021/formulas/mathematics/college/dj16942qga4o33jq93ufh0t9gllmc2f57u.png)
Explanation:
Hello,
(1) 2x + 4y + z = 3
(2) x - 2y - 3z = 4
(3) x + y - z = -1
From (3) we can write z = x + y + 1 and we replace in (1)
2x + 4y + x + y + 1 = 3 <=> 3x + 5y = 3-1 =2
(1') 3x + 5y = 2
and we replace in (2)
x - 2y -3(x+y+1) = 4 <=> -2x -5y -3 = 4 <=> -2x -5y = 4 + 3 = 7
(2') -2x - 5y = 7
(1') + (2') gives
3x - 2x + 5y - 5y = 2 + 7 = 9
x = 9
we replace in (1')
3*9 + 5y = 2 <=> 27 + 5y = 2 <=> 5y = 2-27 = -25 <=> y = -25/5 = -5
y = -5
and then in (3)
9 - 5 - z = -1 <=> 4 - z = -1 <=> z = 4 + 1 = 5
z = 5
hope this helps